Organized smallholders’ knowledge and attitude toward oil palm farmland biodiversity and willingness to participate in sustainable palm oil certification in Felda Layang-Layang, Johor - Wagimin, Nurul Izati (2016)
Although biodiversity will undoubtedly be higher in natural forest systems than other forest systems, carefully designed oil palm landscapes may provide some opportunities for the conservation of forest wildlife species outside protected areas. Palm oil sustainability standards and certifications have been introduced to oil palm growers to provide the sustainable management of oil palm plantation with biodiversity conservation. The problem is the certification was not parallel with the smallholders’ acceptance. The objectives of this study were to determine smallholders’ knowledge and attitude towards biodiversity in oil palm oil farmland and to determine smallholders’ attitude and willingness to participate in sustainable palm oil palm certification. Convenience sampling was applied to collect data for a period of four weeks. Fifty usable questionnaire forms were obtained from FELDA Layang-layang, Johor. In order to achieve the objectives, descriptive analysis was conducted to describe smallholders’ background and to estimate the knowledge, attitude and willingness to pay to participate in biodiversity conservation and sustainable palm oil certification schemes (SPOCS). One sample t-test analysis was employed to compare the net revenue per hectare between the organized smallholders from this study and the estate and independent smallholders of previous study. The test also used to compare the annual fee between this study and the RSPO’s fee. Our result showed that most of the smallholders were knowledgeable and have some positive attitudes on conserving biodiversity. Ninety percent of the smallholders agreed to follow the requirements and willing to pay the SPOCS if it is ideal and affordable to them to enhance sustainable oil palm farmland, which is a good sign for better implementation of the SPOCS. By joining any SPOCS, the smallholders not only can gain knowledge about biodiversity but also can increase the net revenue of their crops yield.